2007
DOI: 10.1021/bp070046x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Fed Batch Experiment Design for Estimation of Monod Kinetics of Azospirillum brasilense: From Theory to Practice

Abstract: In this paper the problem of reliable and accurate parameter estimation for unstructured models is considered. It is illustrated how a theoretically optimal design can be successfully translated into a practically feasible, robust, and informative experiment. The well-known parameter estimation problem of Monod kinetic parameters is used as a vehicle to illustrate our approach. As known for a long time, noisy batch measurements do not allow for unique and accurate estimation of the kinetic parameters of the Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Estimating parameters to describe Monod growth and substrate utilization kinetics from experimental data is problematic due to the potential colinearity of max and K s (41). Other investigators have demonstrated that optimal experimental conditions can be established to limit the colinearity of max and K s , thus rendering those parameters identifiable (42,43). Optimal conditions are based on ratios between the initial cell and substrate concentrations and the magnitude of max and K s .…”
Section: Low-concentration Incubation Experimentsmentioning
confidence: 99%
“…Estimating parameters to describe Monod growth and substrate utilization kinetics from experimental data is problematic due to the potential colinearity of max and K s (41). Other investigators have demonstrated that optimal experimental conditions can be established to limit the colinearity of max and K s , thus rendering those parameters identifiable (42,43). Optimal conditions are based on ratios between the initial cell and substrate concentrations and the magnitude of max and K s .…”
Section: Low-concentration Incubation Experimentsmentioning
confidence: 99%
“…The closer these initial values approach the true values, the better the obtained OED will be. OED is, therefore, an iterative procedure (Box and Lucas, 1959;Cappuyns et al, 2007;Franceschini and Macchietto, 2008d;Walter and Pronzato, 1990). OED can also be employed for designing parallel experiments (Galvanin et al, 2007).…”
Section: Optimal Experimental Design and Measurement Techniquesmentioning
confidence: 99%
“…Later on, this concept was further improved and investigated in detail (Asprey and Macchietto, 2000;Fedorov, 1975a, 1975b;Burke et al, 1997;Draper and Hunter, 1966;Hill, 1978;Kremling et al, 2004;Walter and Pronzato, 1990). In all cases OED requires interactions between modeler and experimenter since a compromise between maximum information content and practical feasibility has to be achieved (Cappuyns et al, 2007).…”
Section: Optimal Experimental Design and Measurement Techniquesmentioning
confidence: 99%
“…10,30 The difficulties were either no single solution or insufficient accuracy. [31][32][33] To address the nonlinear features of kinetics in cell culture, neural networks were used to simulate the kinetic model. 8,9 Although neural networks were able to simulate time profiles of variables in cell culture, they were unable to estimate parameters in a physiological sense.…”
Section: Introductionmentioning
confidence: 99%